PENGARUH KARAKTERISTIK INDIVIDU, IKLIM KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA CV. YADNYASESA SUKAWATI - Anak Agung Dewi Widya Sarawati; Ni Wayan Eka Mitariani; I Gede Yudhi Hendrawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Every company needs employees who will provide performance that exceeds the company’s expetations. Performancecan affect the ongoing activities of a company, the better the performance shown by employes, the more helpful it will bein company’s development. In this case, it is necessary to have the role of the company in creating individualcharacteristics, a good work climate, and compensation in order to improve employee performance. This study aims toknow the effect of individual characteristics, work climate, and compensation on employess performance at CV.Yadnyasesa Sukawati. The population in this study were all employees at CV. Yadnyasesa Sukawati, totaling 33 female employees. The sample size was determined using a saturated sample technique where all members of the populationwere sampled, namely 33 employees. The results of this study indicate that Individual Characteristics, Work Climate, andCompensation have a positive and significant effect on the decline on employee performance.